The cost of not wanting to know – the professions, money laundering and organised crime. Issue 1 (2nd January 2018) - Murray, Kenneth
Abstract : Purpose: This paper aims to advocate the development and re-emphasis of "epistemic virtue" in relevant professional ethical codes so that attention is re-focussed on the responsibility of relevant professionals to close windows of opportunity for financial wrongdoing and money laundering that are left open through the widespread practice of "wilful blindness". Design/methodology/approach: This study is an exploration of the duty to know or find out in the accountancy profession via discussion and illustration of how failures in this field contributed to the financial crash; a relation of these failures to "seek the truth" to the concept of "epistemic virtue"; and a discussion of how a lack of epistemic virtue is a necessary condition for the successful practice of money laundering. Findings: This paper considers the case for establishing a new framework for recalibrating the professional ethic model so that the primacy of outward looking attitudes to knowledge is re-established at the heart of professional ethics. Research limitations/implications: The paper advocates the adoption of specific training on outward looking epistemic values in all financially related professional bodies. Practical implications: Review of ethical standards in the professions is required to ensure epistemic virtues are given due weight and prominence within them. Social implications: The accumulation of criminal capital under legitimate guises by serious organised crime requires poses an ongoing threat to the integrity of economic markets. A key step to improving defences against this threat is the elevation of epistemic virtue in the professions. Originality/value: To raise awareness and prominence of epistemic virtue as a necessary component of professional integrity.